Cystic fibrosis and AA amyloidosis: a survey in the French cystic fibrosis network. (December 2014) - Stankovic Stojanovic, Katia; Hubert, Dominique; Leroy, Sylvie; Dominique, Stephane; Grenet, Dominique; Colombat, Magali; Clement, Annick; Fayon, Michael; Grateau, Gilles
Abstract Introduction: To define the characteristics of CF patients developing AA amyloidosis. Methods: A 30-year retrospective survey conducted within the national French CF network to identify cases of CF associated with AA amyloidosis. Results: Nine cases of AA amyloidosis were identified (CF prevalence in France is approximately 6000 patients) and sufficient data were collected in six. The clinical presentation was renal disease in four cases, a compressive goiter in one case, and epigastric pain in one case. Organ involvement included kidney disease in all cases (proteinuria, with a median age at onset of 24 years, 4 cases with nephrotic syndrome, 5 with renal failure); gastrointestinal (4 cases with duodenal ulcer); thyroid (2 cases); and hepatobiliary system (3 cases). The median age at diagnosis of CF was 6.5 years. Five patients had pancreatic insufficiency. All patients had chronic respiratory infections requiring intravenous antibiotics several times a year. Five patients have died, at a median age of 29 years and a median duration of 6 years after the onset of proteinuria. Conclusion: AA amyloidosis is a rare but morbid complication of CF. Renal involvement is predominant.